The effect of chamomile (Matricaria recutita L.) infusion on blood glucose, lipid profile and kidney function in type 2 diabetic patients: a randomized clinical trial - Kaseb, Fatemeh; Yazdanpanah, Zeinab; Naghdipour Biregani, Akram; Barkhordari Yazdi, Nahid; Yazdanpanah, Zakieh (Progress in Nutrition, 2018)
Introduction: Chamomile is one of the medicinal herbs, frequently used in traditional medicine for treatment of diabetes. Therefore this study aimed to evaluate the effects of chamomile herbal tea on glycemic index, lipid profile and kidney function in type 2 diabetic patients. Methods: This randomized clinical trial was conducted on 50 diabetic patients. The intervention group received standard treatment with orally 200 ml/day of chamomile infusion (10 g/100 mL boiling water) twice a day before meals (lunch and dinner) for 4 weeks. The control group only received standard therapy. Results: Consumption of the chamomile infusion was accompanied by a significant reduction in total cholesterol (TC) (p= 0.02), low density lipoprotein cholesterol (LDL-C) (p= 0.04) and creatinine (Cr) (p= 0.03). Within-group comparisons showed there was a significant decrease in fasting blood sugar and 2-h postprandial glucose in the intervention group (p= 0.01), (p= 0.03), respectively. Conclusions: Chamomile has potential desirable effects on serum levels of TC, LDL-C and Cr  in patients with type 2 diabetes taking oral hypoglycemic agent.